Did Australia's Baby Bonus Increase the fertillity Rate? - Warren, D; Wooden, M; Sawyer, K; Sheffler, K; Drago, R (My University, 2009)
In May 2004, the Australian government announced a “Baby Bonus” policy, paying women an initial A$3,000 per new child. We use household panel data from the Household, Income and Labour Dynamics in Australia Survey (N = 14,932) and a simultaneous equations approach to analyze the effects of this bonus on fertility intentions and ultimately births. The results indicate that opportunity costs influence intentions and births in predictable ways. Fertility intentions rose after the announcement of the Baby Bonus, and the birth rate is estimated to have risen modestly as a result. The marginal cost to the government for an additional birth is estimated to be at least A$124,000.
Melbourne Institute of Applied Economic and Social Research Working Paper Series No. 1/09
Keywords: Benefits and Payments; Families -- Fertility; Families; Benefits and Payments -- Family payments; Income, wealth and finances; Families and relationships; Families and relationships; Income, wealth and finances